Fiscal policy, banks and the financial crisis - Robert Kollmann; Marco Ratto; Werner Roeger; Jan in't Veld (National Bank of Belgium, 2012)
This paper studies the effectiveness of Euro Area (EA) fiscal policy, during the recent financial crisis, using an estimated New Keynesian model with a bank. A key dimension of policy in the crisis was massive government support for banks—that dimension has so far received little attention in the macro literature. We use the estimated model to analyze the effects of bank asset losses, of government support for banks, and other fiscal stimulus measures, in the EA. Our results suggest that support for banks had a stabilizing effect on EA output, consumption and investment. Increased government purchases helped to stabilize output, but crowded out consumption. Higher transfers to households had a positive impact on private consumption, but a negligible effect on output and investment. Banking shocks and increased government spending explain half of the rise in the public debt/GDP ratio since the onset of the crisis.
Keywords: E62; E32; G21; H63; F41; 330; financial crisis; bank rescue measures; fiscal policy; Finanzkrise; Finanzpolitik; Staatliche Einflussnahme; Finanzsektor; Bank; Bankenkrise; Schuldenübernahme; Wirkungsanalyse; Eurozone